International Student’s Survival Guide - McDonald, Ian (Journal of International Students, 2015)
This guide, by Gareth Davey, is aimed at both those considering studying in the UK and those already doing so, with much of the material relevant to both groups. Whilst clearly aimed at students, the publication will also be useful to members of staff who work, or are looking to work, with international students. The book will help staff develop a greater appreciation of the issues and concerns international students face whilst studying abroad, for example, cultural differences between the UK and students’ home countries and the processes international students have to go through to gain entry onto UK degree programmes.